2006
DOI: 10.1073/pnas.0510816103
|View full text |Cite
|
Sign up to set email alerts
|

A yeast assay probes the interaction between botulinum neurotoxin serotype B and its SNARE substrate

Abstract: The seven functionally distinct serotypes (A-G) of botulinum neurotoxin (BoNT) are dichains consisting of light chain (LC) with zinc-dependent endoprotease activity connected by one disulfide bond to heavy chain with neuronal-cell translocation and receptorbinding domains. LC-mediated proteolysis of soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins and consequent inhibition of synaptic vesicle fusion to the presynaptic membrane of human motor neurons are responsible for fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In an overnight assay, 0.01 pmol of LC/A1 cleaved 25% of the available SNAP25, while 0.1 pmol of BoNT/A4 did not yield detectable cleavage of SNAP25 (< 2% cleavage, the limit of resolution) (data not shown). Controls showed that BoNT/B in the partially purified toxin preparation cleaved VAMP under standard assay conditions (25), indicating that the partial purification did not intrinsically inactivate the toxins. This is consistent with the native BoNT/A4 possessing a limited capacity to cleave SNAP25 relative to the A1 serotype.…”
Section: Resultsmentioning
confidence: 99%
“…In an overnight assay, 0.01 pmol of LC/A1 cleaved 25% of the available SNAP25, while 0.1 pmol of BoNT/A4 did not yield detectable cleavage of SNAP25 (< 2% cleavage, the limit of resolution) (data not shown). Controls showed that BoNT/B in the partially purified toxin preparation cleaved VAMP under standard assay conditions (25), indicating that the partial purification did not intrinsically inactivate the toxins. This is consistent with the native BoNT/A4 possessing a limited capacity to cleave SNAP25 relative to the A1 serotype.…”
Section: Resultsmentioning
confidence: 99%
“…Regions of BoNT involved in SNARE recognition and cleavage have been identified [ 78 , 79 ], including the residues directly involved in catalysis [ 80 ], although residues both near and distal to the active site are reported to be important in their proteolytic action [ 81 , 82 ]. Primary sequences are also now available for 36 human SNAREs [ 76 ] and mapping the sites cleaved by members of the clostridial neurotoxins family has been completed ( Table 3 ) [ 83 , 84 ].…”
Section: Modifying the Bont Active Site To Target Non-native Substmentioning
confidence: 99%
“…Residues highlighted by circles using the same color code depict to what extent introduction or reversal of charges affects cleavage. Data from the following publications were incorporated into this scheme: [ 44 , 65 , 70 , 73 , 81 , 90 , 91 , 92 , 93 ]. In case of divergent data on mutants, averaged values are shown.…”
Section: Mode Of Substrate Recognitionmentioning
confidence: 99%